Acid Violence in South Asia: A Structural Analysis toward Transformative Justice. Issue 1 (June 2017) - Kuriakose, Francis; Mallick, Neha; Iyer, Deepa Kylasam
Acid violence is embedded in larger macro-political and economic structures that sustain gender domination and perpetuate new forms of gender inequality. This article argues that increasing incidences of acid violence in South Asia and especially in India would benefit from the structural analysis that takes into account impacts from socio-economic structures that reinforce gender inequality. In contemplating a systemic redress mechanism, structural analysis is used to enlarge legal norms. The article proposes a model of transformative justice that involves centrality of state responsibility as a catalyst for social change.